The Bloomsbury introduction to postmodern realist fiction resisting master narratives - T.V. Reed; Bloomsbury Academic (London; New York; New Delhi; Oxford; Sydney Bloomsbury Academic, 2021)
Postmodern realist fiction uses realism-disrupting literary techniques to make interventions into the real social conditions of our time. It seeks to capture the complex, fragmented nature of contemporary experience while addressing crucial issues like income inequality, immigration, the climate crisis, terrorism, ever-changing technologies, shifting racial, sex and gender roles, and the rise of new forms of authoritarianism. A lucid, comprehensive introduction to the genre as well as to a wide variety of voices, this book discusses more than forty writers from a diverse range of backgrounds, and over several decades, with special attention to 21st-century novels. Writers covered include: Kathy Acker, Chimamanda Ngozi Adiche, Julia Alvarez, Sherman Alexie, Gloria Anzaldua, Margaret Atwood, Toni Cade Bambara, A.S. Byatt, Octavia Butler, Angela Carter, Ana Castillo, Don DeLillo, Junot Diaz, Jennifer Egan, Awaeki Emezi, Mohsin Hamid, Jessica Hagedorn, Maxine Hong Kingston, Ursula K. Le Guin, Daisy Johnson, Bharati Mukherjee, Toni Morrison, Vladimir Nabokov, Tommy Orange, Ruth Ozeki, Ishmael Reed, Eden Robison, Salman Rushdie, Jean Rhys, Leslie Marmon Silko, Art Spiegelman, Kurt Vonnegut, and Jeannette Winterson, among others.
Includes bibliographical references (pages 258-268) and index (269-275).
Keywords: Criticism, interpretation, etc; Fiction; Fiction History and criticism .